OBSERVATIONS OF 231PA235U DISEQUILIBRIUM IN VOLCANIC ROCKS - Pickett D.A.; Murrell M.T. (My University, 1997)
We present here the first survey of (231Pa235U) ratios in volcanic rocks; such measurements are made possible by new mass spectrometric techniques. The data place new constraints on the timing and extent of magma source and evolutionary processes, particularly due to the sensitivity of the 231Pa-235U pair and its intermediate time scale (231Pa t12 = 33 ky). (231Pa235U) is found to vary widely, from 0.2 in carbonatites to 1.1-2.9 in basalts and 0.9-2.2 in arcs. Substantial Pa enrichment is nearly ubiquitous, suggestive of the relative incompatibility of Pa, qualitatively consistent with available partitioning data. The level of 231Pa-235U disequilibrium typically far exceeds that of 230Th-238U and is comparable to226 Ra-230Th. The high (231Pa235U) ratios in MORB and other basalts reflect a large degree of discrimination between two incompatible elements, posing challenges for modelling of melt generation and migration. Fundamental differences in (231Pa235U) among different basaltic environments are likely related to contrasts in melting zone conditions (e.g., melting rate). Strong (231Pa235U) disequilibria in continental basalts, for which (230Th238U) disequilibria are small or absent, demonstrate that Pa-U fractionation is possible in both garnet and spinel mantle stability fields. In arcs, correlation of (231Pa235U) and (230Th238U) is consistent with U enrichment via slab-derived fluids, a process which is additional to the still dominant Pa enrichment. An important new constraint is provided by the observation that the near-equilibrium (230Th238U) common to arcs and continental basalts is not typically accompanied by near-equilibrium (231Pa235U), arguing against the influence of long magma history, crustal material, or equilibrium mantle sources in affecting decay-series ratios. Small sample sets from two silicic centers illustrate: (1) recent, rapid U enrichment in the magma chamber (El Chichon); and (2) the failure of substantial magma H2O-CO2 degassing to effect U-Th-Pa fractionation (Mono Craters).
Keywords: URANIUM DISEQUILIBRIUM; PROTACTINIUM; MAGMAS; ISOTOPES; BASALTS; ISLAND ARCS